2021
DOI: 10.3389/fcvm.2021.749592
|View full text |Cite
|
Sign up to set email alerts
|

Incidence- and In-hospital Mortality-Related Risk Factors of Acute Kidney Injury Requiring Continuous Renal Replacement Therapy in Patients Undergoing Surgery for Acute Type a Aortic Dissection

Abstract: Background: Few studies on the risk factors for postoperative continuous renal replacement therapy (CRRT) in a homogeneous population of patients with acute type A aortic dissection (AAAD). This retrospective analysis aimed to investigate the risk factors for CRRT and in-hospital mortality in the patients undergoing AAAD surgery and to discuss the perioperative comorbidities and short-term outcomes.Methods: The study collected electronic medical records and laboratory data from 432 patients undergoing surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 50 publications
(59 reference statements)
3
12
0
Order By: Relevance
“…Some conventional risk factors that have been known to be associated with worse outcomes after ATAAD surgery, including preoperative sCr, preoperative CRP, prolonged CPB times, and PMV also predicted the requirement for CRRT as suggested in our study and other previous studies ( 37 ). Compare to traditional indicators, the measurement of lactate has several advantages: rapidity, simplicity, convenient, and capability of repeated assessments.…”
Section: Discussionsupporting
confidence: 83%
“…Some conventional risk factors that have been known to be associated with worse outcomes after ATAAD surgery, including preoperative sCr, preoperative CRP, prolonged CPB times, and PMV also predicted the requirement for CRRT as suggested in our study and other previous studies ( 37 ). Compare to traditional indicators, the measurement of lactate has several advantages: rapidity, simplicity, convenient, and capability of repeated assessments.…”
Section: Discussionsupporting
confidence: 83%
“…Evidence from the previous studies reported the incidence of postoperative CRRT use in patients undergoing surgery with aTAAD was 11-27%, and the mortality in such patients was significantly higher than in patients who were not. [63][64][65] Our study confirmed these phenomena. We performed concomitant CABG in two clinical scenarios, type B and type C coronary artery involvement clarified via intraoperative exploration 66 and difficult CPB weaning considered to be related to insufficient coronary artery blood flow.…”
supporting
confidence: 88%
“…The role of obesity in aortic disease has been controversial. Several previous studies have shown that obesity was not significantly associated with mortality through aortic dissection but only increases perioperative complications and ventilation time ( 7 , 41 , 42 ). The BMI of patients also had no effect on the early major adverse outcomes and mid-term survival by continuous grouping ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 95%